N TYPE SiC SINGLE CRYSTAL SUBSTRATE AND SiC EPITAXIAL WAFER
Patent Information
- Application Number
- JP2024212468
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2042-06-02
AI Technical Summary
【0022】 本発明のn型SiC単結晶基板によれば、8インチのSiC単結晶基板であって、高いドーパント濃度でかつ濃度分布ばらつきが抑制されたn型SiC単結晶基板を提供できる。
Smart Images

Figure 2025023296000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an n-type SiC single crystal substrate, an SiC epitaxial wafer, and an n-type SiC single crystal ingot. [Background technology]
[0002] Silicon carbide (SiC) has an electric breakdown field one order of magnitude larger than silicon (Si) and a band gap three times larger. Silicon carbide (SiC) also has properties such as a thermal conductivity about three times higher than silicon (Si). For this reason, silicon carbide (SiC) is expected to be applied to power devices, high-frequency devices, high-temperature operating devices, and the like. For this reason, SiC epitaxial wafers have come to be used in the above-mentioned semiconductor devices in recent years.
[0003] SiC epitaxial wafers are obtained by stacking a SiC epitaxial layer on the surface of a SiC single crystal substrate. Hereinafter, the substrate before the SiC epitaxial layer is stacked is referred to as a SiC single crystal substrate, and the substrate after the SiC epitaxial layer is stacked is referred to as a SiC epitaxial wafer. SiC single crystal substrates are cut from SiC single crystal ingots.
[0004] The current market mainstream for SiC single crystal substrates is 6-inch (150 mm) in diameter, but development is also underway for mass production of 8-inch (200 mm) SiC single crystal substrates, and full-scale mass production is about to begin. With the improvement in production efficiency and cost reduction achieved by increasing the diameter from 6 to 8 inches, it is expected that SiC power devices will become even more widespread as a trump card in energy-saving technology.
[0005] When manufacturing the next generation of large-diameter SiC single crystal substrates, the same quality cannot be obtained even if the manufacturing conditions optimized for the manufacturing of the current diameter SiC single crystal substrate are applied. This is because new problems arise according to the new size. For example, Patent Document 1 describes a problem that when manufacturing a 4-inch SiC single crystal substrate in the manufacturing of a 6-inch SiC single crystal substrate, thermal decomposition frequently occurs around the outer periphery of the seed crystal, which causes macro defects, and therefore single crystals with high crystal quality cannot be obtained with a good yield. Patent Document 1 describes an invention that solves the problem by using a seed crystal with a specified thickness. In this way, it is necessary to establish manufacturing conditions for SiC single crystal substrates of new sizes while solving new problems that arise according to the new size.
[0006] In SiC devices as power semiconductors, it is very important to increase the doping concentration and reduce resistance in order to reduce loss. Also, to reduce the characteristic variability between SiC devices, it is necessary to minimize the variability in dopant concentration. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Patent No. 6594146 [Patent Document 2] Patent No. 6598150 [Patent Document 3] JP 2020-17627 A [Patent Document 4] JP 2019-189499 A Summary of the Invention [Problem to be solved by the invention]
[0008] SiC single crystal substrates are obtained through a SiC single crystal ingot production process and a SiC single crystal substrate process in which SiC single crystal substrates are produced from the SiC single crystal ingots. Establishing the manufacturing technology for 8-inch SiC single crystal substrates requires solving new issues unique to 8-inch substrates in both the SiC single crystal ingot production process and the SiC single crystal substrate process.
[0009] Here, new challenges unique to 8-inch substrates include, for example, obtaining an 8-inch substrate with the same dislocation density as that of a 6-inch substrate in the SiC single crystal ingot manufacturing process. If an 8-inch substrate is manufactured by simply applying a manufacturing technology for SiC single crystal substrates optimized for manufacturing 6-inch substrates, the resulting 8-inch substrate will have a higher dislocation density than that of a 6-inch substrate. This is because the hurdle to obtain the same quality increases significantly as the size increases. Therefore, when evaluating manufacturing technology for 8-inch SiC single crystal substrates, the starting point is the dislocation density of an 8-inch substrate obtained by simply applying a manufacturing technology for SiC single crystal substrates optimized for manufacturing 6-inch substrates, and the value of the technology should be evaluated based on the degree of improvement based on the dislocation density at the starting point. On the other hand, the yield of 8-inch SiC single crystal substrates in mass production is determined by evaluation standards that are the same as those for 6-inch SiC single crystal substrates or stricter standards. Step-by-step improvements will lead to the establishment of manufacturing technology for 8-inch SiC single crystal substrates.
[0010] Furthermore, in order to meet the increasing demand for power semiconductors, it is essential to establish the manufacturing technology for 8-inch SiC single crystal substrates as well as the technology to achieve high dopant concentrations while suppressing variation in concentration distribution.
[0011] The present invention has been made in consideration of the above circumstances, and has an object to provide an 8-inch SiC single crystal substrate, an n-type SiC single crystal substrate having a high dopant concentration and suppressed variation in concentration distribution, and a SiC epitaxial wafer. [Means for solving the problem]
[0012] In order to solve the above problems, the present invention provides the following means.
[0013] A first aspect of the present invention is an 8-inch n-type SiC single crystal substrate having a diameter in the range of 195 to 205 mm and a dopant concentration of 2×10 18 / cm 3 That's it, 6 x 10 19 / cm 3 or less, and the dopant concentration at at least five points in the radial direction, including points within 1 mm from the outermost circumference, is within ±20% of the dopant concentration at the in-plane center at the same depth from the main surface.
[0014] A second aspect of the present invention is an n-type SiC single crystal substrate according to the first aspect, wherein the dopant concentration at at least five radial points, including points within 1 mm from the outermost circumference, is within ±15% of the dopant concentration at the in-plane center at the same depth from the main surface.
[0015] A third aspect of the present invention is an n-type SiC single crystal substrate according to the first or second aspect, wherein the dopant concentration at at least five radial points, including points within 1 mm from the outermost periphery, is within ±10% of the dopant concentration at the in-plane center at the same depth from the main surface.
[0016] A fourth aspect of the present invention is an n-type SiC single crystal substrate according to any one of the first to third aspects, wherein the dopant is nitrogen.
[0017] A fifth aspect of the present invention is a SiC epitaxial wafer comprising an n-type SiC single crystal substrate according to any one of the first to fourth aspects, and a SiC epitaxial layer laminated on a surface of the n-type SiC single crystal substrate.
[0018] A sixth aspect of the present invention is an n-type SiC single crystal ingot, wherein a substrate having a diameter in the range of 195 to 205 mm is cut out from the n-type SiC single crystal ingot, and a dopant concentration of the cut out substrate is measured, and the dopant concentration is 2×10 18 / cm3 That's it, 6 x 10 19 / cm 3 The n-type SiC single crystal ingot has a dopant concentration within ±20% at at least five radial points, including points within 1 mm from the outermost circumference, relative to the dopant concentration at the in-plane center at the same depth from the main surface of the cut out substrate.
[0019] A seventh aspect of the present invention is an n-type SiC single crystal ingot according to the sixth aspect, wherein the dopant concentration at at least five radial points, including points within 1 mm from the outermost circumference, is within ±15% of the dopant concentration at the in-plane center at the same depth from the main surface of the cut out substrate.
[0020] Aspect 8 of the present invention is an n-type SiC single crystal ingot according to aspect 6 or aspect 7, wherein the dopant concentration at at least five radial points, including points within 1 mm from the outermost circumference, is within ±10% of the dopant concentration at the in-plane center at the same depth from the main surface of the cut out substrate.
[0021] A ninth aspect of the present invention is the n-type SiC single crystal ingot according to any one of the sixth to eighth aspects, wherein the dopant is nitrogen. Effect of the Invention
[0022] According to the n-type SiC single crystal substrate of the present invention, it is possible to provide an 8-inch SiC single crystal substrate having a high dopant concentration and suppressed variation in concentration distribution. [Brief description of the drawings]
[0023] [Figure 1] 1A is a schematic cross-sectional view of a SiC single crystal substrate according to this embodiment, and FIG. 1B is a schematic plan view. [Diagram 2] 1A is a schematic cross-sectional view of a SiC single crystal substrate according to this embodiment, and FIG. 1B is a schematic plan view. [Diagram 3] This is a conceptual diagram showing the definition of SORI. [Figure 4]1 is a conceptual diagram showing a process in which the depth of a work-affected layer is reduced by mechanical processing. FIG. [Diagram 5] FIG. 1 is a schematic cross-sectional view of a SiC single crystal manufacturing apparatus. [Figure 6] FIG. 2 is a schematic cross-sectional view of another example of a SiC single crystal growing apparatus. [Figure 7] 2 is a schematic cross-sectional view of a driving means for vertically moving a heat insulating material in a SiC single crystal manufacturing apparatus. FIG. [Figure 8] The figure shows the relative positions of the bottom surface of the insulation material and the surface of the single crystal, as well as the relationship with the isothermal surface in the vicinity of the single crystal. [Figure 9] FIG. 2 is a schematic diagram showing the shape of an isothermal surface in the vicinity of a single crystal during crystal growth. [Figure 10] FIG. 2 is a schematic plan view showing an example of a 10 mm square mesh. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0024] The present invention will be described in detail below with reference to the drawings as appropriate. The drawings used in the following description may show characteristic parts in an enlarged scale for the sake of convenience in order to make the features of the present invention easier to understand, and the dimensional ratios of each component may differ from the actual ones. The materials, dimensions, etc. exemplified in the following description are merely examples, and the present invention is not limited thereto. The present invention may be practiced with appropriate modifications within the scope of the effects of the present invention. In addition, in each drawing, components well known to those skilled in the art other than the components illustrated in that drawing may be omitted.
[0025] (SiC single crystal substrate) FIG. 1(a) is a schematic cross-sectional view of a SiC single crystal substrate according to this embodiment, and (b) is a schematic plan view. The SiC single crystal substrate 1 shown in FIG. 1 is an 8-inch n-type SiC single crystal substrate, with a diameter in the range of 195 to 205 mm, a thickness in the range of 300 to 650 μm, a process-affected layer on both the front and back surfaces having a thickness of 0.1 nm or less, and a dopant concentration of 2×10 18 / cm 3 That's it, 6 x 10 19 / cm 3The following is the result.
[0026] There is no particular limitation on the external shape of the SiC single crystal substrate 1, and various flat plate shapes and thicknesses can be used, but a typical shape is a disk. The thickness of the SiC single crystal substrate can be in the range of 300 to 650 μm, for example.
[0027] The SiC single crystal substrate 1 is preferably 4H-SiC, because although there are various polytypes of SiC, 4H-SiC is primarily used to fabricate practical SiC devices.
[0028] One surface of the SiC single crystal substrate 1 is the surface (main surface) on which the SiC epitaxial layer is formed, and it is preferable that the main surface is the c-plane (the (0001) surface of the 4H-SiC crystal) or a surface obtained by inclining the c-plane at an inclination angle (off angle) of more than 0 degrees and less than 10 degrees. It is a 4H-SiC type single crystal wafer. The off angle is preferably more than 0 degrees and less than 10 degrees with the c-plane in the <11-20> direction. The larger the off-angle, the fewer the number of wafers that can be obtained from a SiC single crystal ingot, so a small off-angle is preferable from the viewpoint of cost reduction. For example, a SiC single crystal substrate with an off-angle of 0.4° to 5° can be used. 0.4° can be said to be the lower limit of the off-angle at which step-flow growth can be performed.
[0029] The n-type dopant may be, in general, nitrogen, but is not limited to nitrogen.
[0030] The dopant concentration of the SiC single crystal substrate 1 is 2×10 18 / cm 3 That's it, 6 x 10 19 / cm 3 The following is the result. The dopant concentration of the SiC single crystal substrate is 2×10 18 / cm 3 If the dopant concentration is less than 6×10, the resistivity of the SiC single crystal substrate becomes too high. 19 / cm 3If the dopant concentration of the SiC single crystal substrate exceeds 2×10, it becomes difficult to suppress stacking faults in the SiC single crystal substrate. 18 / cm 3 That's it, 6 x 10 19 / cm 3 By setting the thickness within the following range, it is possible to reduce the resistivity while suppressing stacking faults in the SiC single crystal substrate. The dopant concentration can be adjusted by a known method, for example, by adjusting the amount of dopant gas introduced into the crucible (see reference numeral 10 in FIG. 5) during crystal growth by adjusting the introduction time, partial pressure, etc.
[0031] Within a surface 1A within 5% of the plate thickness from the main surface 1a of the SiC single crystal substrate 1 in the depth direction, at least five arbitrarily selected points are selected to have a dopant concentration of 2×10 18 / cm 3 That's it, 6 x 10 19 / cm 3 It is preferable that: FIG. 1 illustrates nine points, including the in-plane center O, as measurement points for the dopant concentration in the surface 1A.
[0032] In the SiC single crystal substrate 1, the dopant concentration at at least five radial points, including point p1 within 1 mm from the outermost circumference 1b, is preferably within ±20%, more preferably ±15%, and even more preferably ±10% relative to the dopant concentration at the in-plane center at the same depth from the main surface 1a. In FIG. 1, reference numeral 1bb denotes a circle 1 mm from the outermost periphery 1b.
[0033] The in-plane distribution of the dopant concentration can be adjusted by a known method. For example, in order to make the amount of dopant supplied to the outer periphery higher than the amount of dopant supplied to the inner periphery, a flow path for dopant gas is provided in the crucible (see reference numeral 10 in FIG. 5) and the gas permeability of the crucible is adjusted to make the amount of dopant supplied to the outer periphery higher than the amount of dopant supplied to the inner periphery. In addition, for example, the amount of dopant supplied to the outer periphery can be adjusted by providing an opening in a guide member (see reference numeral 20 in FIG. 5 and reference numeral 25 in FIG. 6) or by adjusting the thickness of the guide member.
[0034] FIG. 2(a) is a schematic cross-sectional view of the SiC single crystal substrate according to this embodiment, and (b) is a schematic plan view. In SiC single crystal substrate 1 shown in FIG. 2, when surface 1AA at the same depth from main surface 1a is divided into meshes M of 10 mm square, and the dopant concentration at any point within each mesh is defined as the dopant concentration of that mesh, it is preferable that the proportion of meshes whose dopant concentration is within ±20% of the dopant concentration of mesh M0 including the in-plane center is 80% or more.
[0035] The dopant concentration can be measured by secondary ion mass spectrometry (SIMS).
[0036] The SiC single crystal substrate 1 has process-affected layers on both the front and back surfaces each having a thickness of 0.1 nm or less.
[0037] The main surface (hereinafter sometimes referred to as the "front surface") of the SiC single crystal substrate 1 is a mirror surface. This is because the front surface of the SiC single crystal substrate needs to form a SiC epitaxial layer by epitaxially growing a SiC single crystal in order to fabricate various SiC devices. Therefore, the front surface is formed by cutting the substrate (a portion that will become the substrate) from a SiC single crystal ingot manufactured by sublimation method or the like, and mirror-finishing the surface of the cut substrate. The other surface (hereinafter sometimes referred to as the "rear surface") does not have to be a mirror surface, but a SiC single crystal substrate with a mirror surface on the front side and a non-mirror surface on the back side has a problem in that a difference in residual stress occurs between the front side and the back side, causing the substrate to warp to compensate for the residual stress (the Twyman effect). By making the back side a mirror surface as well, it is possible to suppress the warping of the substrate caused by the Twyman effect. A method has been developed for producing a SiC single crystal substrate with little warping, even when the front side is a mirror surface and the back side is not a mirror surface (see, for example, Patent Document 2).
[0038] The SiC single crystal substrate 1 has a notch 2 which serves as an indicator of the crystal orientation, but may have an OF (orientation flat) instead of the notch 2.
[0039] The SORI of the SiC single crystal substrate 1 is preferably 50 μm or less, more preferably 40 μm or less, even more preferably 30 μm or less, and most preferably 20 μm or less.
[0040] SORI is one of the parameters that indicate the degree of warping of a substrate, and is expressed as the sum of the normal distances from a least-squares plane calculated by the least-squares method using all data on the substrate surface when the substrate is supported on the back side and measured without changing the original shape, to the highest and lowest points on the substrate surface. In other words, as shown in Figure 3, if the least-squares plane on the substrate surface is set as the reference height (least-squares plane height), SORI represents the sum ((a) + (b)) of the distance (a) between the height of the highest point on the substrate surface and the reference height, and the distance (b) between the height of the lowest point and the reference height.
[0041] <Relationship between processing-affected layer and SORI> SiC single crystal substrates are made by slicing a SiC single crystal ingot and flattening the surface. This type of mechanical processing introduces processing strain into the surface of the substrate. The part of the surface of the SiC single crystal substrate where processing strain occurs is called the processing-affected layer. When processing-affected layers are present on the front and back surfaces, differences in processing strain occur between the front and back surfaces, which also cause differences in residual stress, causing the substrate to warp due to the Twyman effect. The shape (warping) of the substrate is determined by the balance of the stress states generated by the processing-affected layers on both sides of the substrate.
[0042] Figure 4 is a conceptual diagram showing the process by which the depth d of the damaged layer (d1, d2, d3, d4) is reduced by mechanical processing. For example, (a) is a cross section near the surface after lapping, (b) is polishing, (c) is finish grinding, and (d) is CMP.
[0043] FIG. 14 of Patent Document 3 shows the relationship between the depth of the process-affected layer and the SORI of a single crystal SiC wafer. According to this graph, the deeper the process-affected layer, the larger the SORI value. In addition, when comparing a 6-inch SiC single crystal substrate with a 4-inch SiC single crystal substrate, the 6-inch SiC single crystal substrate is more susceptible to the effect of the process-affected layer and has a larger SORI. From this, it is presumed that when comparing an 8-inch SiC single crystal substrate with a 6-inch SiC single crystal substrate, the 8-inch SiC single crystal substrate is more susceptible to the effect of the process-affected layer and has a larger SORI. Therefore, it is more important to remove the process-affected layer in order to reduce warpage for an 8-inch SiC single crystal substrate than for a 6-inch SiC single crystal substrate.
[0044] The SiC single crystal substrate 1 has an in-plane variation in substrate thickness of 2.0 μm or less. The in-plane variation in thickness is preferably 1.5 μm or less, and more preferably 1.0 μm or less. In the SiC single crystal substrate according to this embodiment, a novel lapping slurry is used for lapping, thereby realizing a reduction in in-plane variation in thickness.
[0045] In this specification, "in-plane variation in substrate thickness" refers to the difference between the maximum and minimum values measured by measuring the thickness of a SiC single crystal substrate using a dial gauge or the like at five points (one point at the center and four points on a circumference of a (1 / 2) radius circle (positions at the inclination angles of 0°, 90°, 180°, and 270°)
[0046] FIG. 14 of Patent Document 3 shows the relationship between the depth of the process-affected layer, which is one parameter of the process-affected layer, and the SORI. In developing an 8-inch SiC single crystal substrate with a high yield, the present inventor focused on the in-plane variation in the depth of the remaining process-affected layer. Even if the process-affected layer can be almost completely removed when the planarization process is performed over a sufficient time period at the laboratory level, it is assumed that some of the process-affected layer will remain when the planarization process is performed in a practical time period. In addition, the depth d of the process-affected layer conceptually shown in FIG. 3 is drawn assuming an average depth, but in reality, it does not remain at a strictly uniform depth, and it is thought that the process-affected layer remains thinly over the entire surface with some in-plane depth variation, or that the process-affected layer remains locally within the surface. In such a case, it is presumed that the effect of the in-plane variation in the depth of the process-affected layer on the SORI will be greater in the case of an 8-inch SiC single crystal substrate than in the case of a 6-inch SiC single crystal substrate. It is believed that the in-plane variation in the substrate thickness of the SiC single crystal substrate 1 reflects the in-plane variation in the depth of the process-affected layer.
[0047] The SiC single crystal substrate 1 has a micropipe defect density of 1 / cm 2 It is preferable that:
[0048] The total number of etch pits that appeared after KOH etching on the SiC single crystal substrate 1 was 5 × 10 9 Preferably, 5×10 or less. 8 It is more preferable that the number is 5×10 or less. 7 In this case, the KOH etching was performed at 550° C. for 10 minutes. The total number of etch pits corresponds to the total number of dislocations.
[0049] The SiC single crystal substrate 1 has an etch pit density of 2×10 3 pieces / cm 2 The density of etch pits identified as basal plane dislocations is 5×10 3 pieces / cm 2 It is preferable that: The density of etch pits identified as threading dislocations (TDs) is 1×10 3 pieces / cm 2 More preferably, it is 5×10 or less. 2 pieces / cm 2 It is even more preferable that: The density of etch pits identified as basal plane dislocations is 2×10 3 pieces / cm 2 More preferably, it is 1×10 3 pieces / cm 2 More preferably, it is 5×10 or less. 2 pieces / cm 2 More preferably, it is: Here, the threading dislocation refers to a combination of threading screw dislocations (TSDs) and threading edge dislocations (TEDs). The type of dislocation can be identified from the shape of the etch pits that appear after KOH etching using an optical microscope, and the number of etch pits per unit area can be counted. In general, medium-sized hexagonal etch pits correspond to threading screw dislocations (TSDs), small-sized hexagonal etch pits correspond to threading edge dislocations (TEDs), and elliptical (shell) etch pits correspond to basal plane dislocations (BPDs). Large-sized hexagonal etch pits correspond to micropipes (MPs).
[0050] (Manufacturing method of SiC single crystal substrate) The manufacturing method of the SiC single crystal substrate according to this embodiment will be described by dividing it into the manufacturing process of an n-type SiC single crystal ingot and the manufacturing process of the SiC single crystal substrate from the ingot. In the following, the manufacturing process of an n-type SiC single crystal ingot into which nitrogen is introduced as a dopant will be described as an example.
[0051] <Manufacturing process of n-type SiC single crystal ingot> In the course of continuous intensive research, the inventor has found that in the production of an 8-inch diameter SiC single crystal ingot, more precise control of the temperature gradients in the radial direction and the vertical direction (crystal growth direction) with respect to a 6-inch diameter SiC single crystal ingot is the key point. And by applying the method disclosed in Patent Document 4, it has been found that more precise control of the temperature gradients in the radial direction and the vertical direction (crystal growth direction) can be achieved. Specifically, a SiC single crystal manufacturing apparatus provided with a heat insulating material that can move along the extending direction of the guide member on the outside of the guide member that guides crystal growth can be used. Note that the method for more precisely controlling the temperature gradients in the radial direction and the vertical direction (crystal growth direction) is not limited to the method disclosed in Patent Document 4.
[0052] In the transition period of increasing the diameter of the SiC single crystal ingot, there is a problem that a large-diameter SiC single crystal ingot with the same crystal quality cannot be obtained by applying the manufacturing method of the SiC single crystal ingot of the previous diameter. For example, in the transition period from a 4-inch diameter SiC single crystal ingot to a 6-inch diameter SiC single crystal ingot, there were the following problems (see Patent Document 1).
[0053] In the growth of SiC single crystals by the sublimation recrystallization method using a seed crystal, one of the growth conditions for realizing high crystal quality is that the surface shape of the single crystal ingot during growth must be approximately convex in the growth direction. For example, in the case of 4H-type SiC single crystals used in power devices, <0001> When the SiC single crystal grows approximately parallel to the axis, i.e., the c-axis direction of the crystal, the single crystal grows by the development of spiral steps generated from threading screw dislocations. Therefore, it is said that by making the growth surface approximately convex, the step supply source on the growth surface becomes substantially one point, and polytype stability can be improved. If the growth surface is concave or has multiple apexes, the supply sources of the growth steps become multiple points, which results in a portion where different steps generated from each supply source collide with each other. In such a case, not only do defects such as dislocations occur at the colliding portions, but the atomic stacking state in the c-axis direction specific to the 4H polytype tends to become disordered, resulting in the generation of heterogeneous polytypes with different stacking structures such as 6H type and 15R type, which generates micropipe defects.
[0054] Therefore, for example, in order to stabilize the 4H-type polytype suitable for power devices and grow a so-called single polytype crystal consisting of only the 4H-type polytype, it is important to make the growth surface shape of the grown crystal approximately convex. Specifically, the convex shape of the grown crystal is realized by optimizing the temperature at the center of the grown crystal in terms of the growth rate, etc., and controlling the temperature distribution during growth, i.e., the isothermal shape, to make it approximately convex. It was thought that a SiC single crystal ingot grown under such growth conditions where an approximately convex isothermal line is realized will grow approximately parallel to the isothermal line, thereby ensuring the above-mentioned polytype stability.
[0055] However, when the diameter of the grown crystal is increased to 150 mm (6 inches) or more, if the temperature of the center of the grown crystal is optimized in terms of growth rate and the like to be equivalent to that of conventional 100 mm (4 inch) diameter single crystal growth, while the temperature gradient during growth is controlled so that the growth surface shape of the grown crystal is roughly convex in the growth direction, the temperature of the peripheral portion of the seed crystal inevitably becomes higher than in the case of small diameter crystal growth. As a result, there is a problem that the SiC single crystal of the seed crystal itself is easily thermally decomposed at its outer periphery. Patent Document 1 solves this problem mainly by using a seed crystal made of a silicon carbide single crystal having a thickness of 2.0 mm or more.
[0056] In the present invention, in producing an 8-inch n-type SiC single crystal ingot, a technique that is not used in the typical method for producing a 6-inch n-type SiC single crystal ingot as shown in Patent Document 1 is used, in which a heat insulating material that can move along the extension direction of the guide member that guides the crystal growth is used, and by controlling not only the radial temperature gradient but also the vertical temperature gradient (crystal growth direction), it has been possible to successfully produce an 8-inch n-type SiC single crystal ingot with properties comparable to a 6-inch n-type SiC single crystal ingot. The SiC single crystal production apparatus and the SiC single crystal ingot production process are described below.
[0057] FIG. 5 is a schematic cross-sectional view of an example of a SiC single crystal manufacturing apparatus for carrying out the process of producing an n-type SiC single crystal ingot.
[0058] The SiC single crystal manufacturing apparatus 100 shown in Fig. 5 includes a crucible 10 including a seed crystal installation part 11, a guide member 20, and a heat insulating material 30, a chamber (not shown) for accommodating these, and a gas introduction pipe (not shown) connected to the chamber for introducing nitrogen gas. For ease of understanding, Fig. 5 simultaneously illustrates the raw material G, the seed crystal S, and the single crystal C grown on the seed crystal S. In the following drawings, the direction in which the seed crystal setting part 11 and the raw material G face each other is defined as the up-down direction, and the direction perpendicular to the up-down direction is defined as the left-right direction.
[0059] The crucible 10 surrounds a film-forming space K in which the single crystal C is grown. Any known crucible for producing the single crystal C by a sublimation method can be used for the crucible 10. For example, graphite, tantalum carbide, etc. can be used. The crucible 10 becomes hot during growth. Therefore, it is necessary for the crucible 10 to be made of a material that can withstand high temperatures. For example, graphite has an extremely high sublimation temperature of 3550°C and can withstand the high temperatures during growth.
[0060] The seed crystal mounting part 11 is provided at a position facing the raw material G in the crucible 10. Since the seed crystal mounting part 11 is located at a position facing the raw material G, the raw material gas can be efficiently supplied to the seed crystal S and the single crystal C.
[0061] The guide member 20 extends from the periphery of the seed crystal installation part 11 toward the raw material G. That is, the guide member 20 is disposed along the crystal growth direction of the single crystal C. Therefore, the guide member 20 functions as a guide when the single crystal C grows from the seed crystal S.
[0062] The lower end of guide member 20 is supported by support 21. Support 21 blocks the gap between the lower end of guide member 20 and crucible 10, and suppresses intrusion of source gas into the region outside guide member 20. If source gas intrudes into this region, polycrystals grow between guide member 20 and insulating material 30, preventing free movement of insulating material 30.
[0063] The connection between the guide member 20 and the support 21 is preferably a crimped structure. A crimped structure is a structure designed to tighten the connection between the guide member 20 and the support 21 when a physical force is applied to the guide member 20. For example, a screw structure in which the connection is threaded is an example of a crimped structure. The guide member 20 may come into physical contact with the growing single crystal C, and in such a case, it is possible to prevent the guide member 20 from falling off.
[0064] Guide member 20 in Fig. 5 extends vertically in the up-down direction. The shape of guide member 20 is not limited to this shape. Fig. 6 is a cross-sectional schematic diagram of another example of SiC single crystal manufacturing apparatus 101 according to this embodiment. Guide member 25 in Fig. 6 expands in diameter from seed crystal installation section 11 toward raw material G. By expanding the diameter of guide member 25, the diameter of single crystal C can be increased.
[0065] Although the upper end of guide member 20 in FIG. 5 is open, the upper end of guide member 20 may be connected to the inner surface of crucible 10 to make the space in which heat insulating material 30 exists a closed space.
[0066] The surface of the guide member 20 is preferably coated with tantalum carbide. The guide member 20 is always exposed to the raw material gas in order to control the flow of the raw material gas. If the guide member 20 is used with exposed graphite, the graphite may react with the raw material gas and deteriorate and be damaged. If the guide member 20 is deteriorated and damaged, holes may be formed in the guide member 20. Furthermore, carbon powder peeled off due to deterioration may be taken into the single crystal C, which may lead to deterioration of the quality of the single crystal C. In contrast, tantalum carbide can withstand high temperatures and does not react unnecessarily with the raw material gas. Therefore, high-quality SiC single crystal growth can be performed stably.
[0067] The heat insulating material 30 moves outside the guide member 20 along the extending direction of the guide member 20. By moving the heat insulating material 30, it is possible to control the positional relationship between the end face (hereinafter referred to as the lower face 30a) of the heat insulating material 30 on the raw material G side and the surface Ca of the single crystal C. Therefore, it is possible to freely control the temperature distribution in the vicinity of the surface Ca of the single crystal C, and to freely control the surface shape of the single crystal C that is growing. In the process of crystal growth, the positional relationship between the end face 30a of the heat insulating material 30 on the raw material side and the surface Ca of the single crystal C can be controlled. In addition, during the crystal growth process, the end face 30a of the heat insulating material 30 on the raw material side can be located within 20 mm from the surface Ca of the single crystal C. In addition, during the crystal growth process, the end face 30a of the heat insulating material 30 on the raw material side can be arranged closer to the seed crystal setting part 11 than the surface Ca of the single crystal C. Furthermore, when the thickness of the heat insulating material 30 is 0.2 mm or more, it is possible to reduce this to half or less of the growth amount of the SiC single crystal ingot to be manufactured.
[0068] FIG. 6 is a schematic cross-sectional view of a driving means for moving the heat insulating material 30 up and down. The driving means is not particularly limited as long as it can move the heat insulating material 30 in the up and down direction. For example, as shown in FIG. 6(a), a driving member 31 extending from the top of the heat insulating material 30 to the outside of the crucible 10 may be provided, and the heat insulating material 30 may be moved by pushing and pulling the driving member up and down. Also, as shown in FIG. 6(b), a lifting driving member 32 may be provided to support the heat insulating material 30 from its bottom. Furthermore, as shown in FIG. 6(c), a cut may be provided in a part of the side surface of the crucible 10, and a driving member 33 extending to the outside of the crucible 10 through the cut may be provided, and the heat insulating material 30 may be moved by raising and lowering the driving member.
[0069] The heat insulating material 30 is preferably made of a material having a thermal conductivity of 40 W / mk or less at high temperatures of 2000° C. or more. Examples of materials having a thermal conductivity of 40 W / mk or less at high temperatures of 2000° C. or more include graphite members having a thermal conductivity of 120 W / mk or less at room temperature. More preferably, the heat insulating material 30 is made of a material having a thermal conductivity of 5 W / mk or less at high temperatures of 2000° C. or more. Examples of materials having a thermal conductivity of 5 W / mk or less at high temperatures of 2000° C. or more include graphite and felt materials mainly composed of carbon.
[0070] The shape of the heat insulating material 30 is appropriately designed according to the shape of the area sandwiched between the guide member 20 and the inner surface of the crucible 10. As shown in FIG. 5, when the distance between the guide member 20 and the inner surface of the crucible 10 is constant, the heat insulating material 30 is arranged so as to fill the gap between them. Also, as shown in FIG. 5, when the distance between the guide member 25 and the inner surface of the crucible 10 changes, the shape of the heat insulating material 35 is designed according to the position where the gap between them is narrowest. By designing in this way, it is possible to prevent the heat insulating material 35 from becoming clogged between the guide member 25 and the inner surface of the crucible 10 and becoming stuck.
[0071] The thickness of the heat insulating material 30 is preferably 0.2 mm or more, more preferably 5 mm or more, and more preferably 20 mm or more. If the thickness of the heat insulating material 30 is too thin, it may not be possible to exert a sufficient heat insulating effect. In addition, the thickness of the heat insulating material 30 is preferably half or less of the length of the single crystal finally produced. Here, the single crystal length means the length in the vertical direction of the single crystal C after the crystal growth (the growth amount of the single crystal C). When the growth amount of the single crystal is 100 mm, the thickness of the heat insulating material 30 is preferably 50 mm or less, and when the growth amount of the single crystal is within 50 mm, the thickness of the heat insulating material 30 is preferably 25 mm or less. If the thickness of the heat insulating material 30 is too thick, the movement of the heat insulating material 30 is hindered. Also, if the thickness of the heat insulating material 30 is within the range, a temperature difference can be formed in the vertical direction in the single crystal C via the heat insulating material 30. Therefore, it is possible to prevent the raw material gas from recrystallizing in the portion other than the surface Ca of the single crystal C.
[0072] As described above, the SiC single crystal manufacturing apparatus allows the position of the heat insulating material to be controlled relative to the growing single crystal. By controlling the position of the heat insulating material, the temperature distribution near the surface of the single crystal C during crystal growth can be freely controlled. Since the single crystal C grows along an isothermal surface, controlling the temperature distribution near the surface of the single crystal C leads to controlling the shape of the single crystal C.
[0073] The n-type SiC single crystal ingot can be produced using the above-mentioned SiC single crystal production apparatus. The following describes the case where the SiC single crystal production apparatus 100 shown in FIG. 5 is used as an example.
[0074] In the process of producing an n-type SiC single crystal ingot, a single crystal C is grown from a seed crystal S placed in a seed crystal placement section 11. The n-type single crystal C is grown by introducing nitrogen gas and recrystallizing the raw material gas sublimated from the raw material G on the surface of the seed crystal S. The nitrogen gas reacts on the crystal surface at high temperature, and nitrogen atoms are doped into the SiC single crystal. This nitrogen doping concentration depends on the nitrogen gas concentration, and the higher the nitrogen gas concentration, the higher the doping concentration. The resulting SiC single crystal exhibits a conductivity (resistivity) according to this doping concentration. The raw material G is sublimated by heating the crucible 10 with an external heating means. The sublimated raw material gas is supplied toward the seed crystal S along the guide member 20.
[0075] In the process of producing a SiC single crystal ingot, the positional relationship between the lower surface 30a of the heat insulating material 30 and the surface Ca of the single crystal C is controlled during the process of growing the single crystal C from the seed crystal S. By controlling this positional relationship, the shape of the surface Ca of the single crystal C can be freely controlled.
[0076] Fig. 8 shows the positional relationship between the lower surface 30a of the heat insulating material 30 and the surface Ca of the single crystal C, and the relationship with the isothermal surface near the single crystal C. Fig. 8(a) is an example where the surface Ca (crystal growth surface) of the single crystal C is flat, Fig. 8(b) is an example where the surface Ca (crystal growth surface) of the single crystal C is concave, and Fig. 8(c) is an example where the surface Ca (crystal growth surface) of the single crystal C is convex.
[0077] As shown in Figures 8(a) to 8(c), the shape of the surface Ca of the single crystal C varies depending on the position of the heat insulating material 30 relative to the surface Ca of the single crystal C. As shown in Figure 8(a), when the surface Ca of the single crystal C and the lower surface 30a of the heat insulating material 30 are located at substantially the same position, the surface Ca of the single crystal C is flat. In contrast, as shown in Figure 8(b), when the lower surface 30a of the heat insulating material 30 is located closer to the raw material G than the surface Ca of the single crystal C, the surface Ca of the single crystal C is concave, and as shown in Figure 8(c), when the surface Ca of the single crystal C is located closer to the raw material G than the lower surface 30a of the heat insulating material 30, the surface Ca of the single crystal C is convex.
[0078] The shape of the surface Ca of the single crystal C changes depending on the position of the heat insulating material 30 relative to the surface Ca of the single crystal C because the shape of the isothermal surface T in the film formation space K changes. Fig. 9 is a diagram showing a schematic diagram of the shape of the isothermal surface T in the vicinity of the single crystal C during crystal growth. Fig. 9(a) is a diagram showing the case where the heat insulating material 30 is not provided, and Fig. 9(b) is a diagram showing the case where the heat insulating material 30 is provided.
[0079] The SiC single crystal C has a heat insulating effect by itself due to its low thermal conductivity. On the other hand, the thermal conductivity of the guide member 20 is higher than that of the single crystal C. Therefore, as shown in FIG. 9(a), when there is no thermal insulation material 30, the isothermal surface T is formed to extend from the single crystal C. The crystal growth surface of the single crystal C grows along the isothermal surface T. Therefore, when there is no thermal insulation material 30, the shape of the surface Ca (crystal growth surface) of the single crystal C is fixed to a concave shape.
[0080] In contrast, when a heat insulating material 30 is provided as shown in FIG. 9(b), the shape of the isothermal surface T changes. The shape of the isothermal surface T can be freely designed by controlling the position of the heat insulating material 30 relative to the single crystal C. The design of the shape of the isothermal surface T can be performed with high accuracy by checking in advance by simulation or the like. By controlling the position of the heat insulating material 30 relative to the single crystal C in this manner, the shape of the surface Ca of the single crystal C can be freely designed.
[0081] Furthermore, by controlling the position of the heat insulating material 30 relative to the single crystal C, it is possible to suppress adhesion of polycrystals to the guide member 20 and to reduce the temperature difference in the in-plane direction within the single crystal C.
[0082] Polycrystals are formed in low-temperature areas near the crystal growth surface of single crystal C. For example, as shown in FIG. 9(a), when there is a large temperature difference between single crystal C and guide member 20, polycrystals grow on guide member 20. When the polycrystals grown on guide member 20 come into contact with single crystal C, they disrupt the crystallinity of single crystal C, causing defects. In contrast, as shown in FIG. 9(b), when a heat insulating material 30 is present near surface Ca of single crystal C, the temperature difference between single crystal C and guide member 20 can be reduced, and the growth of polycrystals can be suppressed.
[0083] Furthermore, if there is a large temperature difference in the in-plane direction within the single crystal C, stress is generated during the growth of the single crystal C. Stress generated within single crystal C produces distortion and misalignment of the crystal plane. Distortion and misalignment of the lattice plane within single crystal C can cause killer defects such as basal plane dislocations (BPDs).
[0084] So far, it has been explained that the shape of the surface Ca of the single crystal C can be controlled. The shape of the surface Ca of the single crystal C is preferably flat or convex toward the raw material G. This is because if the shape of the surface Ca of the single crystal C is concave toward the raw material G, the quality is inferior. In order to make the shape of the surface Ca of the single crystal C flat or convex, the position of the surface Ca of the single crystal C and the lower surface 30a of the insulating material 30 are made approximately the same, or the surface Ca of the single crystal C is provided on the raw material G side of the lower surface 30a of the insulating material 30.
[0085] Here, "substantially the same" does not mean that the surface Ca of the single crystal C and the lower surface 30a of the heat insulating material 30 are at exactly the same height, but means that a positional deviation is allowed within a range that does not significantly affect the isothermal surface T. Specifically, if the lower surface 30a of the heat insulating material 30 is located within 30 mm from the surface Ca of the single crystal C, it can be said that the surface Ca of the single crystal C and the lower surface 30a of the heat insulating material 30 are in a substantially identical positional relationship. On the other hand, in order to make the shape of the surface Ca of the single crystal C flat, it is preferable that the positional relationship between the surface Ca of the single crystal C and the lower surface 30a of the heat insulating material 30 is close to being completely the same, and the lower surface 30a of the heat insulating material 30 is preferably located within 20 mm, and more preferably within 10 mm, of the surface Ca of the single crystal C.
[0086] Moreover, the surface Ca of the single crystal C is preferably located closer to the raw material G than the lower surface 30a of the heat insulating material 30. In other words, the lower surface 30a of the heat insulating material 30 is preferably located closer to the seed crystal installation part 11 than the surface Ca of the single crystal C. Even if an external factor such as temperature fluctuation occurs in the film formation space K, the surface Ca of the single crystal C can be prevented from becoming concave.
[0087] Also, the position of the heat insulating material 30 is preferably controlled from the start of crystal growth. That is, at the start of crystal growth, it is preferable to control the positional relationship between the lower surface 30a of the heat insulating material 30 and the surface of the seed crystal S.
[0088] Immediately after the start of crystal growth, the seed crystal placement portion 11 exists around the seed crystal S, and the distance between the seed crystal S and the crucible 10 is also short. Therefore, the isothermal surface T in the film formation space K is also affected by the temperatures (thermal conductivities) of these members. That is, the effect of using the heat insulating material 30 is most exhibited in the region where the single crystal C has grown 30 mm or more from the seed crystal S. On the other hand, it does not mean that the effect of the heat insulating material 30 is not exhibited immediately after the start of crystal growth.
[0089] For example, when the shape of the crystal growth surface of the single crystal C immediately after crystal growth is concave without providing the heat insulating material 30, it is necessary to return the shape of the crystal growth surface of the single crystal C to convex in the subsequent growth process. When the shape of the crystal growth surface changes from concave to convex during the growth process, stress accumulates in the single crystal C, and defects are likely to occur. Therefore, the position of the heat insulating material 30 is preferably controlled from the start of crystal growth. The positional relationship of the heat insulating material 30 with respect to the seed crystal S can be designed in the same manner as the positional relationship between the heat insulating material 30 and the single crystal C during the crystal growth process.
[0090] <Manufacturing process of SiC single crystal substrate> In the process of manufacturing a SiC single crystal substrate from the obtained n-type SiC single crystal ingot, it includes a planarization process including lapping using a predetermined polishing slurry and a process for removing the processed damaged layer. In the manufacture of a SiC single crystal substrate, lapping can be performed using a slurry characteristic in lapping. Otherwise, known methods can be used for the processing from the SiC single crystal ingot until a SiC single crystal substrate is obtained. Hereinafter, the lapping process will be described.
[0091] Next, the lapping slurry that can be used will be described in detail. In the processing step of the free abrasive type, for example, a slurry containing water, boron carbide abrasive grains, and an additive for dispersing the boron carbide abrasive grains is poured between the upper and lower plates, and pressure is applied to the SiC substrate 1 by the upper and lower plates to flatten the surface of the SiC substrate 1. The slurry used in the processing step is, for example, a slurry containing water as a main component. When a slurry containing water as a main component is used, the dispersibility of the boron carbide abrasive grains is increased, and secondary aggregation is less likely to occur in the processing step. In addition, when a slurry containing water as a main component is used, the surface of the SiC substrate on the upper platen side where the slurry supply hole is provided is cleaned by directly supplying water, and the surface on the lower platen side where the slurry supply hole is not provided is cleaned by water supplied through the gap between the SiC substrate and the carrier plate. The slurry used in the lapping process is collected in a tank and supplied again from the tank.
[0092] The modified Mohs hardness (14) of boron carbide abrasive grains is slightly greater than the modified Mohs hardness (13) of a SiC substrate, which is a non-polished object, and is less than the modified Mohs hardness (15) of diamond. Therefore, by using such a slurry, it is possible to relatively increase the processing speed while suppressing the occurrence of cracks in the SiC substrate, which has a modified Mohs hardness (13), and to suppress the reduction in the grain size of the boron carbide abrasive grains.
[0093] The ratio of boron carbide abrasive grains in the slurry is, for example, 15% by mass or more and 45% by mass or less, preferably 20% by mass or more and 40% by mass or less, and more preferably 25% by mass or more and 35% by mass or less. By making the ratio of boron carbide abrasive grains in the slurry 15% by mass or more, the content of boron carbide abrasive grains in the slurry can be increased, and the processing speed of lapping processing can be increased. In addition, by making the ratio of boron carbide abrasive grains in the slurry 45% by mass or less, the frequency and area of contact between boron carbide abrasive grains can be reduced, and it is easy to suppress the reduction in the particle size of boron carbide abrasive grains and the wear of boron carbide abrasive grains.
[0094] The boron carbide abrasive grains in the slurry used in the processing step have, for example, an average particle size of 15 μm or more and 40 μm or less, and preferably 25 μm or more and 35 μm or less. By using boron carbide abrasive grains with an average particle size of 15 μm or more, it is easy to increase the processing speed of lapping the surface of the SiC substrate 1, and further, the additives described later can be sufficiently attached to the surface, which leads to improved dispersibility and suppression of particle size reduction. In addition, by making the average particle size 40 μm or less, it is easy to obtain the effect of suppressing the generation of cracks in the SiC substrate and the cracking of the SiC substrate, and further, it is possible to suppress the excessive attachment of the additives described later to the surface, and it is possible to suppress the decrease in processing speed due to the decrease in the contact area with the SiC substrate as the workpiece. In addition, by using such boron carbide abrasive grains, it is easy to suppress the change in particle size before and after lapping. Here, the average particle size of the boron carbide abrasive grains is the average particle size of the boron carbide abrasive grains before processing, and the average particle size of the boron carbide abrasive grains after processing is, for example, 14 μm or more and 48 μm or less, and preferably 23 μm or more and 42 μm or less, since the ratio of the average particle sizes of the boron carbide abrasive grains before and after processing is 0.91 or more and 1.2 or less.
[0095] Here, the average particle size of the boron carbide abrasive grains is measured based on the particle size distribution measured by laser scattering light measurement using a particle size distribution measuring device Mastersizer Hydro 2000MU (Spectris Corporation) or MT3000II (Microtrack Bell Corporation).
[0096] The additive may be a polyhydric alcohol, an ester and its salt, a homopolymer and its salt, a copolymer, etc. Specific examples include one or more selected from the group consisting of glycerin, 1-vinylimidazole, sodium coconut oil fatty acid methyl taurate, sodium lauric acid amide ether sulfate, sodium myristic acid amide ether sulfate, polyacrylic acid, and an acrylic acid-maleic acid copolymer.
[0097] It is believed that these additives can enhance the dispersibility of the boron carbide abrasive grains in the slurry.
[0098] The additive adheres to the surface of the boron carbide abrasive grains and prevents the boron carbide abrasive grains from directly contacting each other, thus improving the dispersibility of the boron carbide abrasive grains in the slurry and preventing the grain size reduction during the processing step.
[0099] The proportion of additives in the slurry is, for example, 3% by volume or more and 20% by volume or less, preferably 5% by volume or more and 15% by volume or less, and preferably 10% by volume or more and 15% by volume or less. Here, the proportion of additives in the slurry refers to the ratio obtained by dividing the volume of additives (additive components) such as glycerin by the volume of the slurry. When the additives in the slurry are within the above range, they are sufficiently attached to the surface of the boron carbide in the slurry, a preferable degree of dispersion of the boron carbide abrasive grains in the slurry is obtained, and it is easy to suppress the particle size of the boron carbide abrasive grains from decreasing in the processing step.
[0100] In this lapping process, the processing speed for processing the surface of the SiC substrate in the processing step is, for example, 14 μm / h or more and 45 μm / h or less, preferably 16 μm / h or more and 40 μm / h or less, and more preferably 18 μm / h or more and 25 μm / h or less. The processing speed depends on the processing pressure and the average particle size of the boron carbide abrasive grains described above. By setting the processing speed to 45 μm / h or less, it is easy to obtain the effect of suppressing the reduction in the particle size of the boron carbide abrasive grains and the wear of the boron carbide abrasive grains. By setting the processing speed to 14 μm / h or more, the throughput can be increased. When the lapping process is performed in multiple steps, it is sufficient that the processing speed calculated by dividing the total change in the plate thickness of the SiC substrate by the total processing time is within the above range, and it is preferable that the processing speed at each timing is within the above range. That is, when the lapping process is performed in multiple steps, it is preferable that the processing speed calculated in each step is within the above range.
[0101] Here, the processing speed is calculated from the difference in thickness of the SiC substrate 1 before and after the lapping process and the processing time. Specifically, the processing speed is calculated by the following method. The measurement positions of the thickness of the SiC substrate 1 are position 1c corresponding to the center of the SiC substrate before the orientation flat OF is formed on the SiC substrate 1, position 1a 5 to 10 mm away from the midpoint of the orientation flat OF toward position 1c, position 1b on the same line c as positions 1a and 1c and 5 to 10 mm away from the outer periphery of the SiC substrate 1 in the direction of position 1a, and positions 1d and 1e on a line perpendicular to line c and 5 to 10 mm away from the outer periphery of the SiC substrate 1 in the direction of position 1a. The thicknesses of the SiC substrate 1 at these five positions 1a to 1e are measured with an indicator (ID-C150XB, manufactured by Mitutoyo), and the obtained thicknesses are treated as the thicknesses of the SiC substrate 1. The processing speed is calculated by dividing the difference in thickness (μm) of the SiC substrate 1 before and after processing thus obtained by the processing time (h).
[0102] By attaching an additive to the surface of the boron carbide abrasive grains in the slurry used in the processing step, the dispersibility of the boron carbide abrasive grains can be increased and contact of the boron carbide abrasive grains can be suppressed, thereby suppressing reduction in the grain size of the boron carbide abrasive grains. Specifically, the change in the particle size of the boron carbide abrasive grains can be suppressed to a degree that the ratio of the average particle size of the boron carbide abrasive grains after processing to the average particle size of the boron carbide abrasive grains before processing in the processing step is 0.91 or more and 1.2 or less. Here, the reason why the ratio includes a value greater than 1 is that the boron carbide abrasive grains may undergo secondary aggregation in the processing step, and the particle size of some of the boron carbide abrasive grains may become larger than before processing.
[0103] In conventional lapping processes, the particle size of the boron carbide abrasive grains in the slurry is significantly reduced by the lapping process. This means that when lapping is performed again, it is necessary to add abrasive grains to the slurry each time. In addition, each time a complicated management is required to determine the particle size distribution of the abrasive grains in the slurry, which depends on the number of times the slurry has been used for lapping. In this way, this lapping process makes it easy to control the grain size of the boron carbide abrasive grains, reduces costs, reduces the environmental impact, and suppresses the occurrence of cracks.
[0104] In addition, since the grain size of the boron carbide abrasive grains does not change much in this lapping process, the processing speed is prevented from changing during the lapping process, and the lapping process can be continued under the same conditions. This lapping process is particularly effective when using boron carbide as the abrasive grains, which has a slightly higher modified Mohs hardness than silicon carbide as the non-polished object. Since this lapping process uses such abrasive grains and substrate, it is also possible to suppress cracks that frequently occur when diamond is used as the abrasive grains and a SiC substrate is used as the polished object.
[0105] In addition, this lapping process can suppress the grain size reduction and wear of the boron carbide abrasive grains, so the variation in grain size of the boron carbide abrasive grains in the slurry during the lapping process is small. The lapping process speed depends on the grain size of the abrasive grains used, but this lapping process can suppress the variation in grain size of the abrasive grains, so the entire surface of the SiC substrate is processed with abrasive grains of roughly uniform grain size, and the in-plane variation in the substrate thickness of the processed SiC substrate is small. EXAMPLES
[0106] Examples of the present invention will be described below, but the present invention is not limited to the following examples.
[0107] Example 1 First, an n-type SiC single crystal ingot was produced using the SiC single crystal production apparatus shown in Figure 5. First, a 4H-SiC single crystal with a diameter of 200 mm and a thickness of 5.0 mm was used as the seed crystal S, with the (0001) plane as the main surface and an off angle of 4°. In the initial crystal growth, the temperature of the crucible body side wall near the same height as the seed crystal surface (Tr) was 30 to 150°C, the temperature of the seed crystal center in a plan view of the crucible lid outer wall (Tg) was 50 to 250°C, and the temperature difference (ΔT) between Tr and Tg was 20 to 100°C. In accordance with the crystal growth, the heat insulating material 30 was moved stepwise so that the end surface (lower surface) of the heat insulating material 30 on the raw material side was closer to the lid side than the surface of the single crystal, and the distance in the growth direction between the end surface of the heat insulating material 30 on the raw material side and the surface of the single crystal was within 10 mm, and the crystal was grown. In addition, nitrogen gas was introduced at a partial pressure of 554 Pa for 45 minutes when one hour had passed since the start of growth. The n-type SiC single crystal ingot thus obtained had a diameter of 208 mm and a height of 20.2 mm.
[0108] Next, the n-type SiC single crystal ingot was processed by a known method to obtain an 8-inch SiC substrate having a (0001) plane with an off-angle of 4° and a thickness of 0.9 mm.
[0109] The thickness of this SiC substrate was measured. Next, the SiC substrate whose thickness had been measured was placed on the carrier plate of a polishing machine, and lapping was performed. The lapping slurry was obtained by adding a predetermined amount of boron carbide abrasive grains and AD8 (10% by volume) as an additive to water and dispersing them. The boron carbide abrasive grains used had a grain size of F320 (JIS R6001). Here, the proportion of glycerin (manufactured by Aichi Chemitechno Co., Ltd.) as an additive in the slurry was 6% by volume. The lapping process was carried out using a free abrasive method while supplying the lapping slurry at a rate of 16 L / min. The lapping slurry was circulated and used.
[0110] The operating conditions of the polishing device in the lapping process are processing pressure of 160g / cm 2The lower platen rotation speed was 16 rpm, the upper platen rotation speed was 5.5 rpm, the central gear rotation speed was 2.8 rpm, the internal gear rotation speed was 6.0 rpm, and the processing time was 40 minutes. After the lapping process, the particle size distribution of the boron carbide abrasive grains in the slurry was measured in the same manner as before the process, and the plate thickness was measured in the same manner as before the process, and the processing speed was also calculated. In this lapping process, the average processing speed of 15 SiC substrates was 18 μm / h. After the measurement, the slurry used in the previous lapping process was supplied and the second lapping process and measurement were performed while circulating the slurry. In Example 1, this was repeated for a total of eight lapping processes and measurements.
[0111] Next, an etching step for removing a process-affected layer and a CMP step for mirror polishing were carried out to obtain a SiC single crystal substrate of Example 1.
[0112] Example 2 In the production of the SiC single crystal ingot, the temperature of the highest temperature point of the raw material was increased by 20°C, and the operating conditions of the polishing device in the lapping process were adjusted so that the in-plane variation in the substrate thickness after lapping was smaller than in Example 1. Furthermore, except for changing the amount of nitrogen gas introduced, a SiC single crystal substrate was obtained under the same conditions as in the Example.
[0113] Comparative Example 1 A SiC single crystal manufacturing apparatus not having a thermal insulator 30 was used, a seed crystal S having a diameter of 150 mm was used, Tr, Tg, and ΔT were not controlled during crystal growth, a lapping slurry not containing an additive (AD8) was used in the lapping process, and a SiC single crystal substrate was obtained under the same conditions as in the Example, except that the amount of nitrogen gas introduced was changed.
[0114] Comparative Example 2 A SiC single crystal substrate was obtained under the same conditions as in Comparative Example 1, except that the temperature at the highest temperature point of the raw material was increased by 10° C. and the amount of nitrogen gas introduced was changed.
[0115] Comparative Example 3 A SiC single crystal ingot was produced using a SiC single crystal manufacturing apparatus not having a thermal insulation material 30, and a SiC single crystal substrate was obtained under the same conditions as in Example 1, except that in the lapping process, a lapping slurry not containing an additive (AD8) was used and the amount of nitrogen gas introduced was changed.
[0116] (evaluation) The concentration of nitrogen, which is a dopant, at a predetermined point was measured from the stacking surface toward the thickness direction for the SiC single crystal substrates of Example 1, Example 2, and Comparative Examples 1 to 3 using SIMS. The results are shown in Table 1. The nitrogen concentration at each point in Table 1 is the center point O on the surface at a depth of 3 μm, the point p1 at 1.0 mm from the outer periphery, and the three points (p2, p3, p4) that divide the area between them into four equal parts (see FIG. 1). The in-plane average nitrogen concentration in Table 1 is the average nitrogen concentration at these five points, and the nitrogen concentration distribution at the five points indicates the ratio of the difference in nitrogen concentration at the point with the largest difference from the nitrogen concentration at the center among the other four points to the nitrogen concentration at the center. The percentage [%] of the predetermined number of meshes in Table 1 is the percentage of meshes in which the substrate is divided into 10 mm square meshes and the dopant concentration at the center point in each mesh is within ±20% of the dopant concentration of the mesh M0 including the in-plane center. FIG. 10 shows a schematic diagram of the division into 10 mm square meshes. FIG. 10 shows an example of how to divide the 10 mm square mesh, but the invention is not limited to this.
[0117] [Table 1]
[0118] Based on the results shown in Table 1, it can be seen that the nitrogen concentration distribution at five points is reduced in Examples 1 and 2 compared to Comparative Examples 1 to 3. It can also be seen that the proportion of meshes within ±20% of the dopant concentration of mesh M0 including the in-plane center is greater in Examples 1 and 2 compared to Comparative Examples 1 to 3. Thus, in Examples 1 and 2, better nitrogen concentration distribution is obtained over the entire plane compared to Comparative Examples 1 to 3. It is believed that these results are due to the effect that Examples 1 and 2 performed more precise temperature control compared to Comparative Examples 1 to 3, resulting in high-quality SiC single crystals.
[0119] Furthermore, the n-type SiC single crystal substrates of Example 1, Example 2, Comparative Example 1, Comparative Example 2, and Comparative Example 3 were evaluated for SORI, in-plane variation in substrate thickness, number of micropipes, total number of dislocations, threading dislocation density, and basal plane dislocation density. The number of micropipes, total number of dislocations, threading dislocation density, and basal plane dislocation density were evaluated based on etch pits that appeared after KOH etching at 550°C for 10 minutes. The results are shown in Table 2. The TD etch pit density in Table 2 is the combined TSD etch pit density and TED etch pit density.
[0120] [Table 2]
[0121] The micropipe density was 1 / cm in all of Examples 1 and 2 and Comparative Examples 1 to 3. 2 It was as follows. In Examples 1 and 2, both the SORI and the substrate thickness were significantly reduced compared to Comparative Examples 1 to 3. Moreover, in Examples 1 and 2 (8-inch substrate), the total number of etch pits was sufficiently reduced to a degree comparable to that of Comparative Examples 1 and 2 (6-inch substrate), and both the TD etch pit density and the BPD etch pit density were significantly reduced. This result is believed to be the effect of more precise temperature control in Examples 1 and 2. Furthermore, in Examples 1 and 2 (8-inch substrate), the total number of etch pits, the TD etch pit density, and the BPD etch pit density were all significantly reduced compared to Comparative Example 3 (8-inch substrate). This result shows that the effect of more precise temperature control is greater in the production of 8-inch SiC single crystal substrates than in the production of 6-inch SiC single crystal substrates. [Explanation of symbols]
[0122] 1. SiC single crystal substrate
Claims
1. An 8-inch n-type SiC single crystal substrate, The diameter is in the range of 195 to 205 mm, The dopant concentration is 2×10 18 / cm 3 That's it, 6 x 10 19 / cm 3 is as follows: An n-type SiC single crystal substrate, in which the dopant concentration at at least five points in the radial direction, including points within 1 mm from the outermost periphery, is within ±20% of the dopant concentration at the in-plane center at the same depth from the main surface.
2. 2. The n-type SiC single crystal substrate according to claim 1, wherein the dopant concentration at at least five points in the radial direction, including points within 1 mm from the outermost periphery, is within ±15% of the dopant concentration at the in-plane center at the same depth from the main surface.
3. 2. The n-type SiC single crystal substrate according to claim 1, wherein the dopant concentration at at least five points in the radial direction, including points within 1 mm from the outermost periphery, is within ±10% of the dopant concentration at the in-plane center at the same depth from the main surface.
4. 2. The n-type SiC single crystal substrate of claim 1 , wherein the dopant at said dopant concentration is nitrogen.
5. An n-type SiC single crystal substrate according to any one of claims 1 to 4; and a SiC epitaxial layer laminated on a surface of the n-type SiC single crystal substrate.
6. An n-type SiC single crystal ingot, A substrate having a diameter in the range of 195 to 205 mm was cut out from the n-type SiC single crystal ingot, and the dopant concentration of the cut out substrate was measured. 18 / cm 3 That's it, 6 x 10 19 / cm 3 or less, and the dopant concentration at at least five points in the radial direction, including points within 1 mm from the outermost circumference, is within ±20% of the dopant concentration at the in-plane center at the same depth from the main surface of the cut out substrate.
7. 7. The n-type SiC single crystal ingot according to claim 6, wherein the dopant concentration at at least five points in the radial direction, including points within 1 mm from the outermost circumference, is within ±15% of the dopant concentration at the in-plane center at the same depth from the main surface of the cut out substrate.
8. 7. The n-type SiC single crystal ingot according to claim 6, wherein the dopant concentration at at least five points in the radial direction, including points within 1 mm from the outermost circumference, is within ±10% of the dopant concentration at the in-plane center at the same depth from the main surface of the cut out substrate.
9. The n-type SiC single crystal ingot according to any one of claims 6 to 8, wherein the dopant at the dopant concentration is nitrogen.
Citation Information
Patent Citations
Method for manufacturing silicon carbide substrate
JP2014027093A
SiC substrate having SiC epitaxial film
JP2015529015A
Silicon carbide single crystal substrate processing method and silicon carbide single crystal substrate with jig
JP2016032062A
Single crystal sic substrate
JP2017028162A
Method for manufacturing silicon carbide single crystal substrate having low resistivity
JP2017065986A
Cited By
Gallium arsenide single crystal substrate, process for the production of gallium arsenide single crystals and process for the production of gallium arsenide single crystal substrates
DE102026106271A1